Automation System Vibration Analysis Taking Environmental Factors into Consideration - Tian Zhe; Cong Zhang; Xinping Yan; Yeping Xiong (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
This paper aims to investigate the vibration behavior of a propulsion system subjected to hull deformations ina two dimension circumstance. As known that large scale ships have great developments in recent years which could cause much severer conditions among the interaction between the propulsion system and ship hull. Excited forces from thesea waves could make the ship hull deformed which further cause drastic vibrations of the shaft system. As a result, the malfunctions of shaft propulsion system are potential existed as the vibrations of the shaft always exceed its maximum allowable values.This paper establishes a simplified model of the large ship propulsion-hull system to analyze the vibration behavior of the ship propulsion system subjected to the ship hull deformations. The hull deformations were obtained as the excited forces under different sea conditions. Then base on the simplified 2D model, the effects of propeller, supports stiffness, the location of hull excitations, the amplitude of excitations are discussed.